2008
DOI: 10.1177/1043454208323293
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing Psychological Distress During the Diagnosis and Treatment of Pediatric Leukemia

Abstract: A literature review was performed to explore the experiences of parents during their child's diagnosis of leukemia. The findings revealed that anxiety is a major reaction to the diagnosis. Because of the parents' reactions, communication barriers and parental role changes are established between the parent and child. The lack of communication between the parent and child during diagnosis and treatment and parental role changes produce negative outcomes. Negative outcomes place the parent and child at risk for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Previous reports have shown that children and adolescents with ALL manifest high rates of psychological distress as a result of both initial diagnosis and subsequent medical procedures to treat the disease (Kazak et al, 1995; Willingham-Piersol et al, 2008). Adolescent survivors of ALL often manifest higher levels of anxiety in the wake of the disease than their healthy peers (Shelby et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that children and adolescents with ALL manifest high rates of psychological distress as a result of both initial diagnosis and subsequent medical procedures to treat the disease (Kazak et al, 1995; Willingham-Piersol et al, 2008). Adolescent survivors of ALL often manifest higher levels of anxiety in the wake of the disease than their healthy peers (Shelby et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Parental emotional difficulties, such as depression and anxiety, have been reported to decrease after cancer treatment [7,8]. However, many parents continue to experience chronic post-traumatic stress (PTS) for a long time after their child’s treatment [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, even in cultures in which full disclosure is a common practice, parents often find it difficult to tell their child about the disease [20,21]. In western countries, the benefits of truthful disclosure have been examined [8,21,22,23], but there have been few such studies in Japan [24]. …”
Section: Introductionmentioning
confidence: 99%
“… 7 Anxiety is very common in parents of children with leukemia. 8 The researchers reported that relieving parental anxiety could result in positive outcomes for the treatment of their child's leukemia and lessen stress years after treatment. 8 …”
Section: Introductionmentioning
confidence: 99%